Teaching Writing by Using Social Media for High School Students in Indonesia - Ismail, Syofianis; Zaim, M.; Gistituanti, Nurhizrah (J-SHMIC : Journal of English for Academic, 2018)
The purpose of the research is to find out the students’ ability in writing, especially writing recount text by using Facebook as a medium of discussion. In the classroom students set up their Cellphone to write and discuss a recount text. The research question is “Is there any significant effect on students writing recount text by using face book as medium for discussion on Senior High School students?” In the preliminary study it was found that the students’ writing ability was low. Hence, the writer is interested in trying to solve the students’ problem by using Facebook as a medium of discussion. The design of this research was an experimental research. The sample for this research consisted of 25 students. The result of this research found that Facebook as medium for discussion significantly affect the students writing ability. Keywords: facebook, recount text, and medium